(untitled) (Web of Teachers: Inderscience Research, 2023)
This article notes that the demand for innovation is higher than ever in the world today – new knowledge and original technological solutions, analyzed the features and possibilities of introducing an innovative educational cluster in continuing education and the scientific justification of its specific capabilities as the main factors for improving the quality and effectiveness of education in society, as well as the effectiveness of the cluster approach in the school and preschool education system and the task of creating pedagogical innovations as a regional educational cluster and theoretical aspects the development of this area.